2021
DOI: 10.26675/jabe.v6i1.19422
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Indonesian Accounting Education Practices

Abstract: This study reviewed the development of accounting education research in Indonesia for 21 years. The reviews were conducted on 428 accounting education articles in the nationally accredited journals from 1999 to 2019. A bibliometric approach and content analysis were used to analyze the articles’ topics, theories, methods, and characteristics. This study also separated the period of 21 years into two decades. The results show that accounting education research topics revolved on curriculum and teaching, content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…CAR also allows for greater exploration of emergent phenomena, conditions, or information in order to obtain alternative variations for improvement (Syah, 2016). Many researchers in the field of accounting education focus on discussing approaches for teaching using CAR, such as the usage of deep dialogue-critical thinking (DD-CT) learning models, modules, offline and online games, cases, the peer approach, and quantum teaching (Rahmawati & Suryani, 2021). CAR implements improvements of classroom actions for many activities that are conducted with PBL, by which students became able to understand the objectives of PBL.…”
Section: Development Of Publications Of Problem-based Learning Articl...mentioning
confidence: 99%
See 1 more Smart Citation
“…CAR also allows for greater exploration of emergent phenomena, conditions, or information in order to obtain alternative variations for improvement (Syah, 2016). Many researchers in the field of accounting education focus on discussing approaches for teaching using CAR, such as the usage of deep dialogue-critical thinking (DD-CT) learning models, modules, offline and online games, cases, the peer approach, and quantum teaching (Rahmawati & Suryani, 2021). CAR implements improvements of classroom actions for many activities that are conducted with PBL, by which students became able to understand the objectives of PBL.…”
Section: Development Of Publications Of Problem-based Learning Articl...mentioning
confidence: 99%
“…Over time, the variants of research approaches that were utilized by researchers in accounting education became further different. This means that there was an increase in the quality and capabilities of researchers in developing their research according to progressive developments (Rahmawati & Suryani, 2021).…”
Section: Development Of Publications Of Problem-based Learning Articl...mentioning
confidence: 99%
“…Rahmawati conducted a study and found that all types of medicinal plants containing chemical substances that are pharmacologically beneficial, and these plants have a great potential to be transformed into anti-degenerative agents (Rahmawati et al, 2012). WHO also has recommended medicinal herbs to maintain people's health as well as for the prevention and treatment of diseases, especially degenerative diseases and cancer (Setiawati et al, 2016).…”
Section: Introductionmentioning
confidence: 99%